2016
DOI: 10.1089/eco.2015.0059
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Annual Sunlight Opportunity in Domestic Dwellings May Predict Well-Being in Urban Residents in Scotland

Abstract: Well-being and Indoor Sunlight 2 Indoor sunlight improves health in hospitals, schools and workplaces, and there is clinical evidence for the impact on depression, but there is a lack of evidence for a positive impact of sunlight in domestic dwellings on residents' health and well-being. This could have important implications for building design and resident's indoor behavior, and impacts on health. Using a cross-sectional survey we investigated the relationship between annual indoor sunlight opportunity and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This subjective measure of nature near home and the second-most regular location of participants was relevant because it reflects participants' immediate experience of nature on a daily basis. Furthermore, how people perceive 'naturalness' (van den Berg et al 2014), biodiversity (Dallimer et al 2012), and environmental 'quality' (Swanson et al 2015) could have a stronger effect on their wellbeing than ecological descriptors of an environment.…”
Section: Naturementioning
confidence: 99%
“…This subjective measure of nature near home and the second-most regular location of participants was relevant because it reflects participants' immediate experience of nature on a daily basis. Furthermore, how people perceive 'naturalness' (van den Berg et al 2014), biodiversity (Dallimer et al 2012), and environmental 'quality' (Swanson et al 2015) could have a stronger effect on their wellbeing than ecological descriptors of an environment.…”
Section: Naturementioning
confidence: 99%
“… Zhang et al (2017) explored the relationship between air quality and health symptoms though such association proved not significant. In addition, studies have suggested that residents with sufficient sunshine have a higher probability to perceive better health and wellbeing outcomes ( Swanson et al, 2016 ). Residents living in a perceived better maintained environment are also more likely to suffer lower psychological distress compared to residents living in poor quality ones ( Francis et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two overarching factors were considered for assessment of residence suitability: characteristics and assets of the residence itself, and the location of a residence in terms of its relative access to services and amenities. Residence characteristics such as size, age, safety, and privacy can impact resident satisfaction (Gibler et al, 2014;James & Carswell, 2008;Kennedy et al, 2015;Mouratidis, 2020), while aspects like view, noise level, sunlight, and air pollution have additional implications for physical and mental well-being (Bourdrel et al, 2017;Kaplan, 2001;Swanson et al, 2016;Wang & Norbäck, 2021). Access to essential amenities and services such as schools, transit, and recreational spaces like parks have shown to increase neighborhood satisfaction, an indicator of urban livability and quality of life (Mouratidis, 2018(Mouratidis, , 2020.…”
Section: Case Study Of Spatio-temporal Suitability Analysismentioning
confidence: 99%